Advanced spatial modeling with stochastic partial differential equations using R and INLA. (2018) - Krainski, E. T (Elias T.); Gómez-Rubio, Virgilio; Bakka, Haakon; Lenzi, Amanda; Castro-Camilo, Daniela; Simpson, Daniel; Lindgren, Finn; Rue, Håvard
No abstract available